The potential of wind and solar energy for development of hybrid energy system - Nurul Afiqah , Zainal (2013)
This project is motivated by an interest in promoting the use of renewable energy to perform hybrid energy system as one of the alternative to replace the used of gas and coal as the main demand in producing electricity. With depleting local gas reserves and the need to adhere to stricter environmental regulations whilst still having to meet the requirement for growing electricity demand, the consideration of new options in the future generation fuel mix are inevitable. The main purpose of this project is to study on hybrid energy system and the potential of the system to run in UMP, Pekan based on the weather data collected. Two types of energy have been chosen to perform this project which are solar and wind energy. Weather meter and solar equipment are installed to obtain the data within a week and study on the possibilities of both energies if it is installed in this area. The graph shows the data collected within a week and also the highest temperature and wind speed that are captured. Besides that, calculation on types of solar equipment need to be used and wind turbine parameters also been done. Thus, both solar and wind energy able to capture 4W each which gives out total 8W of power produce a day. This is shown that both energies are potential to perform hybrid energy system in UMP Pekan.